Right ventricular pulmonary vascular coupling in secondary tricuspid regurgitation: a pressure volume loop study. (25th November 2020) - Schmeisser, A; Rauwolf, T; Groscheck, T; Tanev, I; Hansen, M; Meissler, S; Steendijk, P; Braun-Dullaeus, R.C
Abstract: Introduction: The severity of secondary tricuspid regurgitation (sTR) predicts outcome of patients with left heart failure with reduced ejection fraction (HFrEF). In these patients sTR predominantly occurs as a result of secondary pulmonary hypertension (PH). However, more than 46% of patients with severe PH have only mild or none sTR. In this study we tested the hypothesis that intrinsic right ventricular (RV) contractility adaptation to the pulmonary arterial (PA) vascular load (RV-PA-coupling) is associated with the presence and severity of sTR. Methods: In 110 patients with HFrEF (a post-hoc analysis of the Magdeburger CRT Responder Trial, DRKS00011133) we quantified the RV intrinsic contractility response (end-systolic elastance, Ees) to pulmonary vascular afterload (arterial elastance, Ea) and its coupling ratio (RV-PA coupling ratio: Ees/Ea) by the RV pressure-volume loop catheter technique at baseline, and combined it with echocardiography-derived parameter of sTR presence and severity and RV function. Results: Echocardiography at baseline demonstrated no or trace TR (TR0) in 67 patients (61%), mild TR (TR1) in 23 (21%), moderate TR (TR2) in 11 (10%), and severe TR (TR3) in 9 (8%). The transition from TR0 to TR1 was characterized by a pronounced drop of the RV-PA coupling ratio (TR0: Ees/Ea= 0.88, 0.67–1.1 vs. TR1: Ees/Ea= 0.48, 0.3–0.83, p<0.001), caused by a non-adaptive, non-rising Ees (0.24 mmHg/ml, 0.34–0.44 vs. 0.3 mmHg/ml, 0.21–0.46, p=0.8, respectively, p<0.001). We observed a further but only marginal drop of Ees/Ea from TR1 to TR3 (p=0.008) caused by an additional small non-significant decrease of Ees and increase of Ea. Interestingly, other afterload parameter, such as PA-pressure, wedge pressure (PCWP), PA compliance, and PA resistance (PVR), and parameters of RV function, such as tricuspid annular plane systolic excursion (TAPSE) and fractional area shortening (FAC) followed the same course of a pronounced drop from TR0 to TR1, succeeded by an only marginal change from TR1 to TR3. In contrast, the progressive RV-PA un-coupling from TR0 to TR3 was accompanied by a more or less continuously increase of RV size and volume load (end-diastolic (ED) area in 4 chamber view, ED-RV outflow tract diameter, size of tricuspid annulus). In the binary logistic regression analysis, the decrease of RV-PA coupling ratio Ees/Ea (OR 0.14, CI 0.001–0.165) and PA compliance (OR 0.44, CI 0.25–0.79) were independently associated with the transition from TR0 to TR1–3. Conclusion: The presence and severity of secondary TR in patients with HFREF is independently associated with a progressive RV-PA uncoupling. Most importantly, already the transition from none TR to mild TR is characterized by a significant and pronounced increase of pulmonary vascular afterload, a non-adaptive RV contractility response, and resulting RV-PA un-coupling. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Boston Scientific